2016
DOI: 10.1080/15384047.2016.1139228
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia regulates ABCG2activity through the activivation of ERK1/2/HIF-1α and contributes to chemoresistance in pancreatic cancer cells

Abstract: Pancreatic cancer is a drug resistant hypovascular tumor. Although there are many studies on the mechanism of chemoresistance in pancreatic cancers, studies on the relationship between ABCG2 and chemoresistance during hypoxia of pancreatic cancer are rare. Hypoxia-inducible factor-1 (HIF-1a) is a master regulator of the transcriptional response to oxygen deprivation in cancer cells. The aim of this study was to examine the role of ABCG 2 and HIF-1a in mediating chemoresistance during hypoxia in pancreatic canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 24 publications
3
49
4
Order By: Relevance
“…S8) (60,61). In particular, a recent study has shown that ABCG2 expression regulates gemcitabine response in pancreatic cancer (62). There is some specificity because we found no correlation between overall survival and the levels of Hippo-independent drug transporters in pancreatic cancers (SI Appendix, Fig.…”
Section: Discussioncontrasting
confidence: 41%
“…S8) (60,61). In particular, a recent study has shown that ABCG2 expression regulates gemcitabine response in pancreatic cancer (62). There is some specificity because we found no correlation between overall survival and the levels of Hippo-independent drug transporters in pancreatic cancers (SI Appendix, Fig.…”
Section: Discussioncontrasting
confidence: 41%
“…A large number of cis-regulatory regions have been identified in or near the promoter region of ABCG2 (reviewed in39). Hypoxia-inducible factor-1 (HIF-1α) stabilizes under hypoxic conditions and has been found to bind to a hypoxia-responsive element in the ABCG2 promoter and increase expression 40,41. Upstream of HIF-1α, signaling via phosphatase and tensin homolog (PTEN), phosphoinositide 3-kinase (PI3K) and protein B kinase (Akt) regulates ABCG2 expression on the cell membrane 4245.…”
Section: Regulation Of Abcg2 Expressionmentioning
confidence: 99%
“…8 As a result, PC cells encounter moderate to extreme hypoxia during the course of their progression, which alter their cellular and behavioral properties. 3,10,11 However, underlying mechanisms remain poorly understood. 3,10,11 However, underlying mechanisms remain poorly understood.…”
mentioning
confidence: 99%